Antifeedant effect of water-soluble anthraquinone pigment of Kerria lacca - Shamim, G; Pandey, DM; Sharma, KK; Ramani, R (Journal of Bio-Science, 2018)
Abstract not available J. bio-sci. 25: 77-81, 2017